Fase nemática biaxial liotrópica : um estudo de parâmetros ópticos - Souza, Gelearde Pereira de (2009)
In this present work, we used refraction index measures of a liquid crystal, which showed the following phase transitions: I-ND-NB-NC-I. However, our interest focused on the nematic biaxial mesophase by presenting possible approaches to analysis by analogy with solid crystals in the same phase. The determination of the angle 2V of indicatrix allowed us to draw important conclusions about the optical signal of the micelle in biaxial phase ([...]), separated by a point defined as optical signal indefinite, and allowed us to do close analysis of phase transitions, ND-NB and NB-NC. Additional measures of density allowed us to observe a small change in the volume near the nematic transitions, which led us to believe that these transitions undergo a change in its geometry, but the change in its volume is almost imperceptible. The optical microscopical analysis of polarized light allowed us to identify each of the stages studied, oriented and not-oriented, and processed by a computer software.